Design and Analysis of a Pre-Engineered Warehouse Building Considering Lateral Load Using Etabs - Anuj Kumar; Afzal Khan; Vikas Patidar (International Journal of Scientific Research in Civil Engineering, 2021)
Pre Engineered Building (PEB) is a concept of performing optimization of structures providing economical design. Steel is a tensile material which provide more strength and available in sections as per requirements. These sections are utilize in pre-engineering building. As per Indian standard I.S 8020:2007 code is prescribed for designing of steel structures. Based on limit state design. P.E.B. structures are high in demand as compared to conventional structure i.e Conventional Steel Building (CSB). CSB design concept is comparatively more easy in fabrication and provide easy restoration. Steel structures are generally utilized in long span structures such as industrial buildings where gantry cranes are installed. Steel structures are easy to assemble in any place as compared to RCC structure where cost and time both are high in comparison. PEB building structure is in demand as it requires less time and provide proper strength. Industrial structures also associate high dead load as it provides residence to heavy sized members. Therefore, this is necessary to investigate seismic response of buildings with various bracings and dampers to control vibration, lateral displacement and storey drift. Natural time period, frequency, roof displacements are the major parameters considered for observing response of structures. Response spectrum analysis of 3D industrial structure with distinct concentric bracings and dampers using SAP 2000 will be carrying in this research under respective base shear . In this study we are comparing different segments of building structure where analysis is performed considering lateral loading condition.